2017
DOI: 10.1007/s11661-017-4053-6
|View full text |Cite|
|
Sign up to set email alerts
|

Thermophysical Properties of Liquid Aluminum

Abstract: Ohmic pulse-heating with sub-microsecond time resolution is used to obtain thermophysical properties for aluminum in the liquid phase. Measurement of current through the sample, voltage drop across the sample, surface radiation, and volume expansion allow the calculation of specific heat capacity and the temperature dependencies of electrical resistivity, enthalpy, and density of the sample at melting and in the liquid phase. Thermal conductivity and thermal diffusivity as a function of temperature are estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 144 publications
(79 citation statements)
references
References 41 publications
(86 reference statements)
13
61
0
Order By: Relevance
“…The new table is compared with that of experiments in the liquid regime in Figure 6. These data have recently been confirmed by Leitner et al [47] Also shown are DFT-MD results by Witte et al [40] The new table agrees well with the PBE calculations, as expected, since it was constructed to match our own PBE calculations in this regime (but not these exact points). The table and the PBE results overestimate the data.…”
Section: F I G U R E 2 (Colour Online) Comparison Of New Table To Dft-mdsupporting
confidence: 85%
See 4 more Smart Citations
“…The new table is compared with that of experiments in the liquid regime in Figure 6. These data have recently been confirmed by Leitner et al [47] Also shown are DFT-MD results by Witte et al [40] The new table agrees well with the PBE calculations, as expected, since it was constructed to match our own PBE calculations in this regime (but not these exact points). The table and the PBE results overestimate the data.…”
Section: F I G U R E 2 (Colour Online) Comparison Of New Table To Dft-mdsupporting
confidence: 85%
“…(Colour online) Solid aluminium resistivity. Shown are experimental points by Brandt and Neuer and a recent set of measurements from Leitner et al, where we have shown the fit given in their paper and the density runs from 2.53 to 2.63 g/cm 3 for the line shown. Two adjacent isochores from the new table are shown (2.7 and 2.4 g/cm 3 ) that should, if the table is accurate, bracket the experimental data.…”
Section: Construction Of Tablementioning
confidence: 65%
See 3 more Smart Citations